Tumour lysis syndrome as a rare complication of chemotherapy in paediatric Wilms’ Tumour: a case report - Qamar, Sobia; Irfana Ishaq Sindhu; Shaheen, Najma (Journal of the Pakistan Medical Association, 2023)
Wilms tumour is the most common renal malignancy in children, with two-thirds of cases diagnosed before five years and 95 percent before 10 years of age. Over the last decade, the five-year survival rate has improved dramatically and now approaches 90 %. Tumour lysis syndrome, commonly seen in association with haematological malignancies, is rarely seen in Wilms tumour. We present two cases of Wilms tumour developing tumour lysis syndrome in the first week of initiation of chemotherapy. Both patients presented with huge abdominal masses causing mass effect on surrounding structures. Chemotherapy was administered as per International Society of Pediatric Oncology guidelines (SIOP). Both patients developed laboratory and clinical tumour lysis syndrome (TLS) after the first cycle of chemotherapy requiring continuous renal replacement therapy (CRRT). However, both died because of multiorgan failure. Key Words: tumour lysis syndrome, Wilms tumour, chemotherapy, continuous renal replacement therapy, case report.